The Acquisition of Relative Clauses in Autism: The Role of Executive Functions and Language. - Peristeri, Eleni; Kamona, Xanthi; Varlokosta, Spyridoula (Journal of Autism & Developmental Disorders, 2024)
Purpose: Relative clauses present a well-known processing asymmetry between object-extracted and subject-extracted dependencies across both typical and atypical populations. The present study aimed at exploring the comprehension of object and subject relative clauses as conceptualized by the Relativized Minimality framework in autistic children and in a group of age- and IQ-matched typically-developing children. The study also explored the way performance in relative clauses would be affected by the children's language and executive function skills. Method: Relative clause comprehension was tested through a sentence-picture matching task and language was tested with a receptive vocabulary task. Executive functions were assessed through backward digit recall and a Flanker test. Results: Object relative clauses were harder to parse for both groups than subject relatives, while number mismatch between the moved object Noun Phrase and the intervening subject Noun Phrase in object relatives boosted both groups' performances. Typically-developing children's performance in object relatives was predicted by both language and executive functions, while autistic children failed to use language and did not systematically draw on their executive functions in object relative clause comprehension. Conclusion: The findings suggest that relative clause processing in autism follows a normal developmental trajectory, and that difficulty with parsing object relative clauses stems from reduced language and executive functions rather than deficits in the children's morphosyntactic skills.